The Effect of Cold Spray on Reducing Pain Levels in Acute Sports Injuries: Case Report - Priambodo, Ayu Prawesti; Cahyani, Gita; Handayani, Nathasa (Media Karya Kesehatan, 2025)
Evidence suggests that cold therapy (cold spray) may be recommended with low confidence for reducing swelling in acute soft tissue injuries among athletes. However, the effect of cold therapy on the mechanical function of muscles remains unclear. This study aims to explore the effects of cold therapy application as a treatment strategy to reduce pan in acute sport injuries. Data collection was conducted in April 2024. We present a case of an acute knee injury in a 16-year-old male during a football tournament. He reported pain with a VAS score of 8 (on a scale of 1 to 10). The patient received cold spray as first aid for his knee injury. However, reassessment revealed that the pain level did not decrease. Several factors may influence the effectiveness of cold spray in reducing pain, including the type of affected nerve fibers, duration of the intervention, history of repeated injuries, size of the injured area, and improper spraying technique. Cold spray is effective in reducing pain and inflammation in superficial tissues. However, in acute injuries involving deeper tissues, cold spray does not significantly alter the pain level. Its effectiveness in reducing inflammatory responses in deeper tissues remains uncertain and warrants further investigation. Keywords: acute pain, cold therapy, foot injury